PERSEPSI SISWA TERHADAP GURU YANG MENGAJAR MENGGUNAKAN CADAR DI SMPN 2 REJANG LEBONG - Abdul Rahman; Lis Diana; Nur Ranni (Universitas Islam Lamongan, 2022)
The results of a preliminary study by researchers in several educational institutions show that not all institutions can accept the presence of teachers wearing the veil. On the one hand, covering aurat is a religious commandment for every Muslim woman; on the other hand, some people are still permissive. This study aims to determine students' perceptions of teachers who teach the veil at SMPN 2 Rejang Lebong. The results of the study show that; 1) There are differences in students' perceptions of the appearance of teachers who use the veil, but these differences will continue to change throughout the interaction with the veiled teacher; 2) Good interaction is a form of adjustment so that the presence of teachers who use the veil at SMPN 2 Rejang Lebong is well received; 3) Good teaching skills by veiled teachers also create a positive impression on students.